Outcomes and mortality risk scoring for infections caused by carbapenem-resistant Escherichia coli and Klebsiella pneumoniae - Jack El Sawda; Jawan Abdulrahim; Rayyan Wazzi Mkahal; George Doumat; Tamara Nawar; Antoine Saliba; Souha S Kanj; Zeina A Kanafani (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant Enterobacterales (CRE) are becoming increasingly prevalent and have been associated with increased mortality. Due to the paucity of data from the region, we evaluated the risk factors and outcomes of infections caused by CRE at a tertiary care center in Lebanon.